The Influence of Intralaminar Damage on Mechanical Properties of Composite Laminates - German, J. (Engineering Transactions, 2004)
In the paper the damage of fiber-reinforced polymeric matrix laminates is considered with the aim to examine the change of their mechanical properties. The damage mode in the form of intralaminar cracks is described in terms of the damage tensor by Vakulenko and Kachanov. The crack discontinuity parameter is estimated in the frames of the linear elastic fracture mechanics. To derive the constitutive relations, which take into account stress, strain and developing damage, an approach based on polynomial invariant functions and irreducible integrity basis by Adkins is employed. Theoretical results are compared with the experimental data obtained for carbon/epoxy laminates.